Aspects of IAIMS Implementation That Require Further Research - Miller, Perry L. (American Medical Informatics Association, 1997)
The Integrated Advanced Information Management System (IAIMS) program promotes an integrated approach to information management within a medical center. Since the IAIMS program was conceived, many of the initial IAIMS technologic needs have been quite widely achieved or are planned for implementation in many medical centers. At the same time, the IAIMS frontier is being steadily pushed to new issues that need to be addressed to achieve the full power of the IAIMS vision. The paper discusses 1) levels of integration where IAIMS has been successfully pursued to date and 2) challenging areas in which research is required to approach the full potential of the IAIMS in the future.